Actors Strategies on Sea Resources Utilization in Pelabuhan Ratu West Java - Royandi, Eva; Satria, Arif; Saharuddin, Saharuddin (Sodality: Jurnal Sosiologi Pedesaan, 2019)
This study aims to (1) analyze the authority of actors to access (control) rights-based marine resources, (2) to analyze the power of actors to access marine resources based on structures and relational resources. This Research was conducted at seawater of Pelabuhan Ratu, Sukabumi, West Java. We use qualitative methods in the present study. The results showed that among local fishers, immigrant fishers (settle), outside fishers (not settle), and managers of the thermal power station (PLTU) have different interests in using marine resources. The Fishers groups have an interest in utilizing marine and fisheries resources (including fishing areas and fish), while PLTU managers have interests in the construction of power plants, barge transportation (coal transportation), development of dams, construction of barge ship ports that buy 3 million seas. The approved PLTU activities must access fisheries against marine resources, coupled with the indication of PLTU waste pollution that harms fishers. The results of the analysis of rights-based licensing for each actor have legislation that is built on official law. The relations of the power's actors to access marine resources based on the structures and relational was held through types of power, i.e., technology, capital, markets, knowledge, authority, social identity and social relationships.